2019
DOI: 10.7554/elife.48434
|View full text |Cite
|
Sign up to set email alerts
|

Retro-2 protects cells from ricin toxicity by inhibiting ASNA1-mediated ER targeting and insertion of tail-anchored proteins

Abstract: The small molecule Retro-2 prevents ricin toxicity through a poorly-defined mechanism of action (MOA), which involves halting retrograde vesicle transport to the endoplasmic reticulum (ER). CRISPRi genetic interaction analysis revealed Retro-2 activity resembles disruption of the transmembrane domain recognition complex (TRC) pathway, which mediates post-translational ER-targeting and insertion of tail-anchored (TA) proteins, including SNAREs required for retrograde transport. Cell-based and in vitro assays sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Absorbance readings were normalized to a vehicle only control, and average of three independent experiments is shown and error bars denote the standard deviation recognition complex (TRC) pathway, which is critical for retrograde transport. 22 In that study, Retro-2 has been shown to interfere with ER targeting of tail-anchored proteins by inhibiting transfer to the ER targeting factor ASNA1. Since the initial submission of this manuscript, the Johannes group, who initially identified Retro-2, has demonstrated that Retro-2.1 binds to the host protein Sec16A.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Absorbance readings were normalized to a vehicle only control, and average of three independent experiments is shown and error bars denote the standard deviation recognition complex (TRC) pathway, which is critical for retrograde transport. 22 In that study, Retro-2 has been shown to interfere with ER targeting of tail-anchored proteins by inhibiting transfer to the ER targeting factor ASNA1. Since the initial submission of this manuscript, the Johannes group, who initially identified Retro-2, has demonstrated that Retro-2.1 binds to the host protein Sec16A.…”
Section: Discussionmentioning
confidence: 97%
“…Several recent studies have advanced our understanding of how Retro‐2 and subsequent optimized compounds protect cells from intoxication. The Bassik group has reported that Retro‐2 compounds protect cells from ricin intoxication by targeting the transmembrane recognition complex (TRC) pathway, which is critical for retrograde transport 22 . In that study, Retro‐2 has been shown to interfere with ER targeting of tail‐anchored proteins by inhibiting transfer to the ER targeting factor ASNA1.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed mechanism was recently provided with the discovery that retro-2 targets the endoplasmic reticulum exit site component Sec16A and affects the anterograde transport of syntaxin 5 from the endoplasmic reticulum to the Golgi [27]. An alternative mechanism was also proposed whereby retro-2 enhances syntaxin 5 degradation and alters its subcellular localization by blocking its delivery to the endoplasmic reticulum targeting factor TRC40, which is required for the insertion of syntaxin 5 into the endoplasmic reticulum [69]. Structure-activity studies to improve the potency of retro analogues were performed, and the best in class molecule is (S) retro-2.1 ( Figure 5), which has an median effective concentration (EC 50 ) of 54 nM against STx in HeLa cells [70,71].…”
Section: Retro-2 Substancesmentioning
confidence: 99%
“…Knowledge of the regulatory mechanisms that control such trafficking suggests that the inhibitory effects of Retro-2 are the result of its actions on various targets. Stx5-dependent effects [29,57,58] relate to a Retro-2-induced default of Stx5 localization to the TGN because it impairs Sec16A-dependent cycling of this SNAREs between the Golgi and the ER [30] and inhibits the ASNA1-mediated ER targeting and insertion of tail-anchored proteins [59]. Moreover, it promoted a default of the docking of EEs carrying Shiga toxin onto the TGN because the EE-associated Shiga toxin-trafficking chaperone GPP130 can no longer bind to its TGN-associated Stx5 receptor [30].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…As a consequence, Retro-2 would be expected to have negative pleiotropic effects and yet, this is not the case [29]. Identical questions have been raised [64] concerning the blocking effect of Retro-2 at the ER [30,59]. For the effect on MT network it is possible that Retro-2 selectively affects one or several existing stable and dynamic sub-populations of αβ-tubulin dimers, or stable MTs with numerous post-translational modifications of tubulin, or various cellular pools of MTs [65,66].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%